2021
DOI: 10.1108/gkmc-09-2021-0146
|View full text |Cite
|
Sign up to set email alerts
|

Journal selection behavior among early-career academicians in Iran: how they choose the most appropriate journal for their publications

Abstract: Purpose Journals are the essential tools of researchers, especially academicians, to present their scientific findings. So, choosing the right journal helps not only science development but also their academic promotion. The purpose of this study is to examine the factors that Iranian medical researchers consider when selecting scholarly journals in which to submit their work. Design/methodology/approach A self-administered online questionnaire was emailed in May 2021, with 101 responses received. The sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…These facts suggested that most researchers in the field of bacterial persisters were more favored to choose reputational and authoritative journals in their research field, not only focusing on IFs. Several other factors also influenced authors to choose journals, including the difficulty of manuscript acceptance, publication charges, time of peer review and so on ( Jiang et al, 2019 ; Shamsi et al, 2021 ). On the other hand, the publication cycle time and circulation time of journals also affected the citations of papers.…”
Section: Discussionmentioning
confidence: 99%
“…These facts suggested that most researchers in the field of bacterial persisters were more favored to choose reputational and authoritative journals in their research field, not only focusing on IFs. Several other factors also influenced authors to choose journals, including the difficulty of manuscript acceptance, publication charges, time of peer review and so on ( Jiang et al, 2019 ; Shamsi et al, 2021 ). On the other hand, the publication cycle time and circulation time of journals also affected the citations of papers.…”
Section: Discussionmentioning
confidence: 99%